0309 Burden of cancer attributable to occupational diesel engine exhaust exposure in Canada0309 Burden of cancer attributable to occupational diesel engine exhaust exposure in Canada. (23rd June 2014) - Kim, Joanne; Peters, Cheryl E; McLeod, Chris; Hutchings, Sally; Rushton, Lesley; Pahwa, Manisha; Demers, Paul A
Abstract : Objectives: To estimate the number of new lung cancers cases in Canada attributable to occupational diesel engine exhaust (DEE), which IARC classified as a definite human carcinogen in 2012. This is part of a larger effort to estimate the current burden of occupational cancers in Canada. Method: Relative risks were selected from two recent studies of miners and truckers with quantitative exposure-response. CAREX Canada estimates of exposure prevalence and level by detailed industry and occupation were supplemented by a literature search for DEE measurement data. For each exposure group, RRs were assigned based upon the estimated mean exposure. Employment trends of industries and occupations were based upon census data from multiple years. Annual Labour Force Survey data were used to attribute age- and tenure-distribution, as well as short-term turnover characteristics. Survival was adjusted to age at entry into the exposed cohort during the risk exposure period 1961–2001. The attributable fraction (AF) for DEE-related lung cancers will be calculated by province, sex, industry and occupation. Results: Approximately 1.4 million workers were exposed to DEE during the risk exposure period. The initial estimated AFs for DEE-related lung cancers are: 4.92% for males, 0.29% for females, and 2.70% overall. Conclusions: These burden estimates are somewhat higher than recent estimates from other groups (1.3–1.8%). They account for the most recent evidence for the risk of lung cancer from occupational DEE exposure, as well as detailed historical exposure assessment and labour force trends. Sensitivity analyses are underway to determine the influential assumptions.